MOLECULAR DOCKING OF GANOMESTENOL WITH SARS-COV-2 MPRO - VENKATESH (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The present study focused on binding mode of the N3 inhibitor and Ganomestenol with receptor SARS-CoV-2 Mpro protease. Methods: The structure of ligands N3 inhibitor and Ganomestenol were designed and 3-D coordinates were prepared using ACD/ChemSketch 8.0 freeware. Autodock4 software was used to study the orientation of the inhibitor or ligand in the active site of biological receptor SARS-CoV-2 Mpro (PDB ID: 6LU7). The Lamarckian genetic algorithm was applied to both ligand and protein for energy minimization using default parameters. The results were analyzed by Ligplot and Pymol software. Results: The compound Ganomestenol designed in in-silico for molecular docking with SARS-CoV-2 protease (Mpro). The in-silico results showed significant binding energy (−6.93 kcal/mol) by comparing with N3 inhibitor (−3.51 kcal/mol). Conclusion: The affinity of Ganomestenol is highly significant compared to N3 inhibitor and also showed efficacy of ligand toward protease under in-silico condition.